2021
DOI: 10.1002/dvg.23459
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the complex genetics of neural tube defects: From biological models to human genomics and back

Abstract: Neural tube defects (NTDs) are a classic example of preventable birth defects for which there is a proven‐effective intervention, folic acid (FA); however, further methods of prevention remain unrealized. In the decades following implementation of FA nutritional fortification programs throughout at least 87 nations, it has become apparent that not all NTDs can be prevented by FA. In the United States, FA fortification only reduced NTD rates by 28–35% (Williams et al., 2015). As such, it is imperative that furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 144 publications
(128 reference statements)
0
20
0
1
Order By: Relevance
“…1. Genetic factors include: 3,4,5,12,13 gene polymorphisms that affect the efficiency of folate metabolism; DNA methylation/ epigenetics; and chromosomal anomalies. use of drugs or alcohol.…”
Section: Factors That Affect Folate Levels In Pregnant Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Genetic factors include: 3,4,5,12,13 gene polymorphisms that affect the efficiency of folate metabolism; DNA methylation/ epigenetics; and chromosomal anomalies. use of drugs or alcohol.…”
Section: Factors That Affect Folate Levels In Pregnant Womenmentioning
confidence: 99%
“…In the United States, folic acid fortification has reduced NTD rates by 28%e35%, with a postdfolate food fortification NTD rate of 1 per 2000 live births. 3,4,5 It has been estimated that of the 4%e5% of babies are born with a serious congenital anomaly (malformation, deformation, or disruption), over half (2%e3% of anomalies) can be identified prenatally through sonographic screening. A further 2% of babies have developmental or functional conditions and minor congenital anomalies that are recognized at birth or during their first year of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward functional testing of SB genetic contributions, the hypotheses generated using systems biology-based computational strategies will require biological validation, likely utilizing genome editing of individual genes and regulatory sequences, singly and in combination, in the mouse in vivo and human stem cell systems (reviewed in ref. 67). These animal and human models offer additional opportunities to test environmental stressors that mimic toxic exposures and intrauterine conditions that undoubtedly interact with the genome and impact the epigenome to tip the epistatic load toward SB (20).…”
Section: Discussionmentioning
confidence: 99%
“…Karzbrun et al found that the width of the nerve tissue determines the shape of the neural tube, and used a chip-based culture system to reconstruct a neural tube in a petri dish that was about 90% similar to that of humans ( 7 ). Wolujewicz et al showed that genetic variation in the genome is an important factor affecting in NTDs ( 8 ). Despite the strengthening of FA treatments in the last 20 years, the incidence of NTDs remains unacceptably high.…”
Section: Introductionmentioning
confidence: 99%